Incorporating numerical method for analyzing the conduction heat transfer during solidification loading nanoparticles - Ahmed Khoshaim; Ali Basem; Hussein A.Z. AL-bonsrulah; Nidal H. Abu-Hamdeh; Sherain M.Y. Mohamed; Ahmad H. Milyani (Case Studies in Thermal Engineering)
This study examines the freezing within a tank with a curved cold surface, integrating an innovative use of fins. The addition of fins and the careful introduction of nanomaterial knowingly enhance solidification efficiency, with potential applications in areas such as cryopreservation and thermal energy storage. To further optimize the solidification process, various types and concentrations of nano-powders were dispersed into the water, serving as heat transfer enhancers. The mathematical model was refined through specific assumptions, leading to the derivation of two principal equations. These equations were then effectively solved using the Galerkin method, offering a novel optimization approach for solidification. The enhancement in conductivity due to the modifications plays a key role in improving the productivity of the system. Furthermore, the addition of nanoparticles resulted in a notable extension of freezing time around 26.71 %. The use of an adaptive grid method during grid generation, coupled with the successful verification of the final model, strengthens the reliability of the research. By increasing the parameter ''m'' (shape factor) from 4.8 to 8.6, the solidification time was reduced by approximately 6.96 %, demonstrating a significant improvement in the system's efficiency.